Ferramenta para planejamento de melhorias para cursos de graduação empregando o IACG - Silva, Sabrina Nogueira (Brasil, 2024)
Assessing the structures, activities and educational processes of a Higher Education Institution (HEI) or a higher education course is essential to identify the gaps that prevent quality education from being offered. This research aims to propose a tool for planning actions to improve the concept of undergraduate courses, using the on-site course evaluation report, based on the Undergraduate Course Evaluation Instrument (IACG) used by the Ministry of Education (MEC). The methodology adopted to carry out the study was bibliographic and documentary research, being applied in an undergraduate course in Production Engineering. The result generated an action plan with suggestions to increase the scores of indicators with performance less than or equal to 3 (satisfactory) to reach the maximum rating of 5 (very good).